Engineered Ovalbumin Nanoparticles for Cancer Immunotherapy. Issue 10 (9th July 2020) - Habibi, Nahal; Christau, Stephanie; Ochyl, Lukasz J.; Fan, Zixing; Hassani Najafabadi, Alireza; Kuehnhammer, Matthias; Zhang, Mengwen; Helgeson, Matthew; von Klitzing, Regine; Moon, James J.; Lahann, Joerg
Abstract: Ovalbumin (OVA) is a protein antigen that is widely used for eliciting cellular and humoral immune responses in cancer immunotherapy. As an alternative to solute OVA, engineering approach is developed herein towards protein nanoparticles (pNPs) based on reactive electrospraying. The resulting pNPs are comprised of polymerized OVA, where individual OVA molecules are chemically linked via poly(ethylene glycol) (PEG) units. Controlling the PEG/OVA ratio allows for fine‐tuning of critical physical properties, such as particle size, elasticity, and, at the molecular level, mesh size. As the PEG/OVA ratio decreased, OVA pNPs are more effectively processed by dendritic cells, resulting in higher OT‐I CD8+ cells proliferation in vitro. Moreover, pNPs with lower PEG/OVA ratios elicit enhanced lymphatic drainage in vivo and increased uptake by lymph node macrophages, dendritic cells, and B cells, while 500 nm OVA pNPs show poor draining lymph nodes delivery. In addition, pNPs with lower PEG/OVA ratios result in higher anti‐OVA antibody titers in vivo, suggesting improved humoral immune responses. Importantly, OVA pNPs result in significantly increased median survival relative to solute OVA antigen in a mouse model of B16F10‐OVA melanoma. This work demonstrates that precisely engineered OVA pNPs can improve the overall anti‐tumor response compared to solute antigen. Abstract : As an alternative to solute antigens for cancer immunotherapy, protein nanoparticles (pNPs) comprised of polymerized antigen linked by poly(ethylene glycol) units are developed based on reactive electrospraying. This engineering approach allows fine tuning the physico‐chemical properties of pNPs such as particle size, elasticity, and mesh size. These properties are related to pNPs enhanced antigen‐specific immune responses and improved anti‐tumor efficacy.